2021
DOI: 10.3389/fpsyg.2021.662050
|View full text |Cite|
|
Sign up to set email alerts
|

Pragmatic Prediction in the Processing of Referring Expressions Containing Scalar Quantifiers

Abstract: Previous research in cognitive science and psycholinguistics has shown that language users are able to predict upcoming linguistic input probabilistically, pre-activating material on the basis of cues emerging from different levels of linguistic abstraction, from phonology to semantics. Current evidence suggests that linguistic prediction also operates at the level of pragmatics, where processing is strongly constrained by context. To test a specific theory of contextually-constrained processing, termed pragma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Research in pragmatics has also been demonstrated to correlate with the clusters identified in our scientometric analysis. Among these studies are those investigating variations in pragmatic language learning in non-English contexts [ 145 ], aspects of politeness [ 146 ], using virtual reality for developing pragmatic language [ 147 ], pragmatics and reasoning [ 148 ], ritual interaction [ 132 ], hearing impairment and pragmatic language skills [ 149 ], autism and neural association of pragmatic language skills [ 150 ], linguistic prediction at the pragmatic language level [ 151 ], mind reading in pragmatics [ 152 , 153 ] and executive functions and pragmatic language skills [ 154 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research in pragmatics has also been demonstrated to correlate with the clusters identified in our scientometric analysis. Among these studies are those investigating variations in pragmatic language learning in non-English contexts [ 145 ], aspects of politeness [ 146 ], using virtual reality for developing pragmatic language [ 147 ], pragmatics and reasoning [ 148 ], ritual interaction [ 132 ], hearing impairment and pragmatic language skills [ 149 ], autism and neural association of pragmatic language skills [ 150 ], linguistic prediction at the pragmatic language level [ 151 ], mind reading in pragmatics [ 152 , 153 ] and executive functions and pragmatic language skills [ 154 ].…”
Section: Discussionmentioning
confidence: 99%